The Efforts to Decriminalize Article 549 of the Indonesian Criminal Code from the Perspective of Islamic Criminal Law - Firmansyah, Puji; Ramadani, Ramadani (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study examines the decriminalization of Article 549 of the Indonesian Penal Code (KUHP) from the perspective of Islamic criminal law, focusing on livestock negligence in Sukadame Village, Silangkitang District, South Labuhan Batu Regency. The issue arises from unconfined livestock damaging private land, leading to legal disputes and calls for regulatory reform. This research aims to analyze the necessity of decriminalizing Article 549 KUHP by evaluating its application in local cases and comparing the legal framework of positive law and Islamic law regarding livestock negligence. A qualitative approach with an empirical juridical method was employed, collecting data through interviews with legal practitioners, community leaders, and affected parties, alongside document analysis. The findings indicate that decriminalizing Article 549 KUHP requires legal reform to ensure alignment with current socio-economic conditions. However, prior to implementation, community engagement is crucial to prevent legal uncertainty and unintended consequences. The study suggests that legal adjustments should balance societal needs and legal enforceability, ensuring fairness while maintaining public order. These findings contribute to ongoing discussions on legal reform in Indonesia, particularly in harmonizing statutory law with Islamic legal principles.